Psychosis and suicide attempt following a single use of delta‐9‐tetrahydrocannabiphorol: A case report - Daniel Greer; Jennifer Atherton; Justina Girgis (PCN Reports, 2025)
Abstract Background Delta‐9‐tetrahydrocannabiphorol (Δ9‐THCP) is a potent phytocannabinoid found naturally in the cannabis plant in small quantities. This cannabinoid is noted to potently bind to cannabinoid receptor 1 and cannabinoid receptor 2 and is reported to be highly psychoactive. A small amount of Δ9‐THCP is found naturally, which led to its isolation and synthetic production. This isolate is beginning to be sold at dispensaries. Information on Δ9‐THCP is sparse and case reports of adverse events add to the current literature. Case Presentation This case report describes a patient who was brought into the emergency department with a self‐inflicted stab wound to the chest after consuming 8 mg of Δ9‐THCP. The patient was a regular user of standard tetrahydrocannabinol (THC) products from dispensaries and had no history of psychotic symptoms. The patient consumed the 8 mg just over 2 days prior to admission and noted psychotic symptoms for 48 h. The symptoms included depersonalization and a belief that he was already dead. A single dose of haloperidol 5 mg intravenous push was administered in the intensive care unit due to agitation. Afterwards, the patient refused all oral antipsychotics and the psychotic symptoms cleared prior to discharge. Conclusion The case adds to the evidence suggesting that Δ9‐THCP is highly potent and psychoactive. Even experienced users of THC may have adverse effects to Δ9‐THCP due to differences in binding and potency. Isolates of phytocannabinoids require caution prior to use.